Pressure-temperature path of arquía group rocks (nw colombia): a petrographic analysis from mineral assemblages (2013)
Based on the type locality mineral associations of the Arquía Group metamorphic rocks in Colombia, the pressure-temperature conditions of metamorphism were obtained and the associated P-T path was built. The analysis of the mineral assemblages indicates a prograde regional metamorphism, which varies from low to medium grade and is represented by greenschist, epidote-amphibolite and amphibolite facies. The results that are based on the prograde mineralogy [actinolite + chlorite + albite + quartz + muscovite + epidote minerals for greenschist facies and hornblende + epidote minerals + garnet + albite ± quartz for epidote-amphibolite and amphibolite facies] indicate a constant increase of metamorphic conditions from 433°C/11.8 kbar to 696°C/14.4 kbar in the metamorphic peak. Retrograde mineral assemblages [muscovite + chlorite + epidote minerals + albite + actinolite] indicate new metamorphic conditions between 417-357°C and 8.1-6.5 kbar. In addition, four deformation events and evidence of shear zone and intracrystalline deformation were found in these rocks. ResumenCon base en las asociaciones minerales existentes en las rocas metamórficas del Grupo Arquía en su sección tipo en Colombia, se determinaron las condiciones de presión-temperatura del metamorfismo y se construyó la trayectoria P-T que siguieron estas rocas. El análisis de las asociaciones minerales es consistente con un metamorfismo regional progrado de bajo a medio grado, representado por facies de esquistos verdes, facies epidota-anfibolita y facies anfibolita. Las asociaciones minerales progradas [actinolita + clorita + albita + cuarzo + moscovita + epidota en facies de esquistos verdes y hornblenda + epidota + granate + albita ± cuarzo en facies epidota-anfibolita and anfibolita] indican un aumento cons- tante en las condiciones del metamorfismo, desde 433°C/11.8 kbar hasta 696°C/14.4 kbar en el pico metamórfico. Las asociaciones minerales retrogradas [moscovita + clorita + epidota + albita + actinolita] señalan nuevas condiciones metamórficas entre 417-357°C y 8.1-6.5 kbar. Adicionalmente, estas rocas evidencian cuatro eventos de deformación, presencia de zonas de cizalla y deformación cristalina.